Pengaruh Penerimaan Retribusi dan Tarif Wisata Air Panas Mengeruda Soa Terhadap Retribusi Daerah Kabupaten Ngada - Wuga, Maria Cresensiana; Londa, Yulita; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2021)
This study aims to determine the partial and simultaneous effect of Receipts and Travel Tariffs on Regional Levies in Ngada Regency. The population in this study are regional levies, tourist levies and tourist tariffs. The samples are budget reports and realization of regional levies, budget reports and realization of tourism levies and tourist tariffs. The research variables consist of regional levies (Y) and retribution receipts (X1) and tourist tariffs (X2). Data analysis using Multiple Linear Regression. The results showed that partially the variable retribution and acceptance of tourism retribution did not have a positive effect on regional levies and simultaneously the variables of tourism retribution and receipt of regional levies had a positive effect on regional levies. Based on the results obtained, it is hoped that it can be used as input in order to increase regional levies from the tourism sector, especially Mengeruda Soa Hot Springs Tourism and it is hoped that the Regional Government will explore sources of income from tourism. The sector is still largely unknown.